Deformability of thick-sheet workpiece in conditions transverse bending - Грушко, О.В.; Молодецька, Т.І. (Problems of Tribology, 2015)
Grushko O. V., Molodeska T. І. Deformability of thick-sheet workpiece in conditions transverse bending.The paper is devoted to the scientific problem of improving the cold bending process for wide workpieces made from low-plasticity metals regarding rational choice of products geometric parameters, prevention of their damage during forming process. Analysis of the stress-strain condition of metal at cold bending wide workpiece is made by computer simulation using the finite element method. Investigated the strain state of the workpiece during transverse bending. The mathematical model of the process of plate bending wide workpieces, allowing to calculate the strain in hazardous areas, in terms of deformability, depending on the basic technological parameters. This makes it possible to generate recommendations for the rational selection of process parameters for the production of parts without the rejection characteristics. It is show that the plasticity chart should be built using the parameter that takes into account the properties of the material. Using this parameter allows higher accuracy to determine the degree of plasticity of the material stock utilization as compared with other charting methods and evaluate the deformability workpiece in transverse bending. Proposed technological solutions aimed at adapting the operations of plate bending pieces of hard materials due to scoring in the blank spot bending. The formulas allowing to calculate the depth of cut depending on the mechanical characteristics of the material and geometrical parameters of the workpiece.